Patience and Comparative Development. (1st December 2021) - Sunde, Uwe; Dohmen, Thomas; Enke, Benjamin; Falk, Armin; Huffman, David; Meyerheim, Gerrit
Abstract: This article studies the relationship between patience and comparative development through a combination of reduced-form analyses and model estimations. Based on a globally representative dataset on time preference in 76 countries, we document two sets of stylized facts. First, patience is strongly correlated with per capita income and the accumulation of physical capital, human capital, and productivity. These correlations hold across countries, sub-national regions, and individuals. Second, the magnitude of the patience elasticity strongly increases in the level of aggregation. To provide an interpretive lens for these patterns, we analyse an overlapping generations model in which savings and education decisions are endogenous to patience, aggregate production is characterized by capital-skill complementarities, and productivity implicitly depends on patience through a human capital externality. In our model estimations, general equilibrium effects alone account for a non-trivial share of the observed amplification effects, and an extension to human capital externalities can quantitatively match the empirical evidence.